The recolonization hypothesis in a full-mouth or multiple-session treatment protocol: a blinded, randomized clinical trial - Zijnge, Vincent; Meijer, Henriette F.; Lie, Mady-Ann; Tromp, Jan A. H.; Degener, John E.; Harmsen, Hermie J. M.; Abbas, Frank (Journal of clinical periodontology, 2010)
Zijnge V, Meijer HF, Lie MA, Tromp JAH, Degener JE, Harmsen HJM, Abbas F: The recolonization hypothesis in a full‐mouth or multiple‐session treatment protocol: a blinded, randomized clinical trial. J Clin Peridontol 2010; 37: 518–525. doi: 10.1111/j.1600‐051X.2010.01562.x. Aim: To test recolonization of periodontal lesions after full‐mouth scaling and root planing (FM‐SRP) or multiple session‐SRP (MS‐SRP) in a randomized clinical trial and whether FM‐SRP and MS‐SRP result in different clinical outcomes. Materials and Methods: Thirty‐nine subjects were randomly assigned to FM‐SRP or MS‐SRP groups. At baseline and after 3 months, probing pocket depth (PPD), plaque index (PlI) and bleeding on probing (BoP) were recorded. At baseline, immediately after treatment, after 1, 2, 7, 14 and 90 days, paper point samples from a single site from the maxillary right quadrant were collected for microbiological analysis of five putative pathogens by polymerase chain reaction. Results: FM‐SRP and MS‐SRP resulted in significant reductions in PPD, BoP and PlI and the overall detection frequencies of the five species after 3 months without significant differences between treatments. Compared with MS‐SRP, FM‐SRP resulted in less recolonization of the five species, significantly for Treponema denticola, in the tested sites. Conclusion: FM‐SRP and MS‐SRP result in overall clinically and microbiologically comparable outcomes where recolonization of periodontal lesions may be better prevented by FM‐SRP.